Czynniki kształtujące konkurencyjność polskiego przemysłu spożywczego - Zuzek, Dagmara K. (Factors Formative Competitiveness in the Polish Food Processing Industry, 2006)
The author pays attention to actions that may constitute a good basis for the Polish food processing industry enterprises order to compete on the EU market. There is a need to maintain the high quality of a product, to use the professional marketing and in particular the strengthening of the brand and the improvement of distribution channels.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 564-569